Barriers and Facilitators to Injection Safety in Ambulatory Care Settings. (4th July 2018) - Leback, Claire; Hoang Johnson, Diep; Anderson, Laura; Rogers, Kelli; Shirley, Daniel; Safdar, Nasia
Abstract : OBJECTIVE: Identify factors referred to as barriers and facilitators that can prevent or assist safe injection practices in ambulatory care settings to guide quality improvement. DESIGN: In this mixed-methods study, we utilized observations and interviews. SETTING: This study was conducted at ambulatory clinics at a midwestern academic medical center from May through August 2017. Sites included a variety of clinical settings that performed intramuscular, intradermal, intravenous, or intra-articular injections. PARTICIPANTS AND INTERVENTIONS: Direct observations of injections and interviews of ambulatory care staff were conducted. An observation checklist was created, including standards of injection safety from nationally recognized guidelines. Interview questions were developed using the System Engineering Initiative for Patient Safety (SEIPS) model. Interviews were recorded, transcribed, and then coded by 2 investigators. RESULTS: In total, 106 observations and 36 interviews were completed at 21 clinics. Injection safety standards with the lowest adherence included using needleless access devices to prepare injections (33%) and the proper use of multidose vials (<80%). Of 819 coded interview segments, 461 (56.3%) were considered facilitators of safe injection practices. The most commonly identified barriers were patient movement during administration, feeling rushed, and inadequate staffing. The most commonly identified facilitators were availability of supplies, experience in the practice area, and availability of safety needles and prefilled syringes. CONCLUSIONS: Perceived barriers and facilitators to infection control elements of injection safety are interconnected with SEIPS elements of persons, organizations, technologies, tasks, and environment. Direct observations demonstrated that knowledge of safety injection standards does not necessarily translate to best practices and may not match self-reported data. Infect Control Hosp Epidemiol 2018;39:841–848